Caring through traditional chinese Medicine - Silva , Shara Vitória Pinto da; Albuquerque Neto , José Fernandes de; Carvalho, Ana Flávia Machado de; Vaz, Isadora Maria Lopes; Mendes, Jucilene de Alencar Sampaio; Costa, Jandson Vieira (Research, Society and Development, 2023)
Pain affects a large part of the population at some point in their lives. Auriculotherapy and cupping therapy are traditional Chinese medicine (TCM) interventions, which are non-drug techniques suggested for the treatment of chronic and psychosomatic pain, among other indications. The study aimed to investigate the effects of auriculotherapy and cupping therapy in the treatment of pain. This is field research, experimental, descriptive, with a quantitative approach, carried out with employees from a Higher Education Institution in Teresina/PI. The volunteers were seen weekly for 10 months and answered two questionnaires, one prepared by the researcher, with personal data and occupation, and the other, the Brief Pain Inventory (IBD), which assessed pain, intensity, anatomical location, and the inference of this symptom on daily life, mood, sleep, work activity and quality of life, was present in the questionnaire, the visual analogue scale (VAS) which aimed to measure the intensity of pain. The questionnaire was applied individually before the first intervention and monthly thereafter. The results of the study showed the effectiveness of the techniques used to treat pain and its impact on the individual's quality of life. It is then suggested to implement these in approaches related to pain, as they are not only simple to apply, they are low cost and their results are efficient.